Geriatric nutritional risk index predicts all-cause mortality in the oldest-old patients with acute coronary syndrome: A 10-year cohort study - Li, Ying; Shen, Jian; Hou, Xiaoling; Su, Yongkang; Jiao, Yang; Wang, Jihang; Liu, Henan; Fu, Zhenhong (Frontiers in Nutrition, 2023)
Background and objective: Nutritional status assessment in acute coronary syndrome (ACS) patients has been neglected for a long time. The geriatric nutritional risk index (GNRI) is a sensitive indicator for assessing the nutritional status of the elderly. This study aims to explore the association between GNRI and all-cause mortality in the oldest-old patients with ACS. Methods: The patients who met the inclusion criteria were consecutively enrolled from January 2006 to December 2012. Clinical data were collected on admission, and all subjects were followed after being discharged. The nutritional status was evaluated using GNRI. The relationship between GNRI and all-cause mortality was assessed by using different analyses. Results: A total of 662 patients with a mean age of 81.87±2.14 years old were included in our study, and followed (median: 63 months, IQR 51-71). Patients whose GNRI≤98 were reported as at risk of malnutrition (31.11%, n=206). In multivariable analysis, we found that for each SD increase in GNRI, the risk of all-cause mortality lowered by 23%, and the HR for GNRI≤98 was 1.39 (95% CI 1.04-1.86). After stratifying patients into three groups by tertiles of GNRI, we found that the HRs for tertile 2 and tertile 3 were 1.49 (95% CI 1.02-2.19) and 1.74 (95%CI 1.22-2.50), respectively. The trend test revealed a dose-response relationship between GNRI and all-cause mortality in the oldest-old with ACS. Lastly, in subgroup analyses, we found a reliable association between GNRI and all-cause mortality. Conclusions: Malnutrition is common in the oldest-old patients with ACS, and GNRI could predict their long-term all-cause mortality in a dose-dependent manner. GNRI may be a prospective index for risk-stratification and secondary-prevention in the oldest-old patients with ACS.